2006
DOI: 10.14411/eje.2006.040
|View full text |Cite
|
Sign up to set email alerts
|

Kairomone involvement in the host specificity of the egg parasitoid Trissolcus basalis (Hymenoptera: Scelionidae)

Abstract: Abstract. This paper reports the results of a comparative laboratory analysis of the behavioural responses of the egg parasitoid Trissolcus basalis (Wollaston) (Hymenoptera: Scelionidae) to semiochemical cues from four species of pentatomid bugs, Nezara viridula (L.), Eurydema ventrale Klt., Murgantia histrionica Hahn. and Graphosoma semipunctatum F. (Heteroptera: Pentatomidae). In a Y-tube olfactometer, T. basalis was attracted by volatile chemicals from N. viridula, but not from other pentatomid species. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…We thus can speculate that host residues might convey to foraging wasp females not only indirect information about host egg presence, but also direct information on the presence of their host species. The actual role of host residues on host specificity of T. basalis was recently addressed by Salerno et al (Salerno et al, 2006), who demonstrated that T. basalis females were able to discriminate between coevolved and non-coevolved host species which may be present on the same infested plants. An analogous situation could be predicted for another egg parasitoid, T. brochymenae, the females of which showed arrestment responses to residues of third and fifth instars, and adults of M. histrionica (Conti et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus can speculate that host residues might convey to foraging wasp females not only indirect information about host egg presence, but also direct information on the presence of their host species. The actual role of host residues on host specificity of T. basalis was recently addressed by Salerno et al (Salerno et al, 2006), who demonstrated that T. basalis females were able to discriminate between coevolved and non-coevolved host species which may be present on the same infested plants. An analogous situation could be predicted for another egg parasitoid, T. brochymenae, the females of which showed arrestment responses to residues of third and fifth instars, and adults of M. histrionica (Conti et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the presence of arresting kairomones has been observed in the following host-egg parasitoid associations: Nezara viridula (L.) -Trissolcus basalis (Wollaston) (Colazza et al, 1999;Salerno et al, 2006), Murgantia histrionica Hahn -Trissolcus brochymenae (Ashmead) (Conti et al, 2003), Eurydema ventrale Klt. -Trissolcus simoni (Mayr) (Conti et al, 2004) and Euschistus heros (F.) -Telenomus podisi (Ashmead) (Borges et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Once the parasitoid is within a potential host community, shape and semivolatile factors increase in importance and when the host is contacted, contact chemicals, shape, size and texture then become important (Vinson, 1984). Scelionidae that parasitize eggs from stink bugs can use several types of semiochemicals for long-range localization of habitat, microhabitat, and hosts: volatiles from plants damaged by stink bug oviposition or feeding Moraes et al, 2005cMoraes et al, , 2008c; sex pheromones (Aldrich, 1995;Borges et al, 1998a,b;2003, Bruni et al, 2000Silva et al, 2006); volatile defensive secretions from the metathoracic (adults) or dorsal abdominal (nymphs) glands of stink bugs (Aldrich 1995, Mattiacci et al, 1993Borges & Aldrich 1992); or crude whole body extracts of stink bugs (Colazza et al 1999;Salerno et al 2006). Volatiles from non-host stages of stink bugs, such as pheromones or defensive compounds, as well as contact chemicals (traces left by walking insects) can also be used for host location, recognition, and acceptance leading to successful oviposition Borges et al, 1999bBorges et al, , 2003Colazza et al, 1999;Conti et al 2003).…”
Section: Stink Bug Semiochemicals and Behavior Of Natural Enemies'mentioning
confidence: 99%
“…The adaptive significance of such behaviour, has been explained in terms of higher probability for host eggs to be found and attacked near traces left by host females that are ready to lay eggs ( Colazza et al , 1999 ). Motivated searching induced by chemical residues left on a substrate by true bugs while moving, has been observed on several other species of Trissolcus and with Telenomus posidi ( Colazza et al , 1999;Borges et al , 2003;Conti et al , 2003Conti et al , , 2004Salerno et al , 2006 ). However, T. basalis females that respond to host female chemical residues and are unsuccessful in locating host eggs during a certain amount of time, gradually lose their arrestment responsiveness (i.e.…”
Section: Introductionmentioning
confidence: 99%